Investigation of Studies on Montessori Method in Turkey - Fatma KOSEOGLU; Yasar BARUT (Yaşam Becerileri Psikoloji Dergisi, 2021)
The Montessori Method is an education system and was created by Maria Montessori. Maria Montessori is an Italian pedagogue and the first female doctor in her country. The Montessori system puts the child in the center and, acting on the principle of relative to the child, is based on an environment created suitable for the child. Considering the interests and abilities of the child, it accepts the individual learning speed and creates a flexible education process based on this. The Montessori method is a synthesis; It aims for children to realize and discover the potential within them and to create their characters. He also argues that the child needs a regulated space and freedom to reach their potential. It is observed that scientific studies on the subject of Montessori are given importance in our country and their studies have increased in recent years. In this study, it is aimed to see the reliability and validity of this method and to give an idea for new researches by examining the theses and articles written between 2010-2021 about the Montessori method and its applications in our country, according to the determined criteria. This study is a qualitative research and criterion learning method and document scanning (analysis) technique, which are purposeful learning strategies, were used. Sources were scanned with the words "montessori" from Google Academy, Dergipark and National Thesis Center data environments, and a total of 84 studies, including 48 thesis studies and 36 article studies, were reached. Considering the findings obtained from the research; It has been determined that the intensity of the studies on the Montessori method in our country belongs to the last 5 years. It can be said that most of the studies were conducted at the preschool level. In the conclusion sections of almost all of the studies, it was stated that a change was observed in favor of the children who received education with the Montessori method.